Neurophysiological assessment of biometric patterns during semi-immersive and traditional learning experiences in the humanities - Romo-De León, Rebeca; Cham-Pérez, Mei Li L.; Elizondo-Villegas, Verónica Andrea; Villarreal-Villarreal, Alejandro; Ortiz-Espinoza, Alexandro Antonio; Vélez-Saboyá, Carol Stefany; Lozoya-Santos, Jorge de Jesús; Cebral-Loureda, Manuel; Ramírez-Moreno, Mauricio A. (Frontiers in Human Neuroscience, 2026)
The use of immersive technologies in education has shown an improvement in the learning process of students. However, applications of these technologies in the Humanities are limited, since most studies focus on scientific fields. In this study, the Neurohumanities Lab was introduced as a semi-immersive space for teaching the Humanities. Two groups of 12 participants each performed activities under the semi-immersive and traditional classroom set-ups, while recording their physiological signals (electroencephalography, electrodermal activity, and heart rate). In both groups, the ITC-SOPI presence questionnaire was used to compare their differences in perceived presence levels, which showed a higher level in the experimental group. Machine learning algorithms were applied, concluding that the decision tree supervised learning model determined the most relevant features to distinguish between both set-ups with an accuracy of 90%. In the experimental group, an increased heart rate was observed with respect to the control group, while the electrodermal activity increased its peaks in both groups compared to the basal state. Additionally, brain source localization techniques revealed a notorious activation of brain areas related to emotional and somatosensory processing during the semi-immersive experience. Therefore, the Neurohumanities Lab has the potential to be a fully immersive environment for innovative education and enhanced learning.